JOB SATISFACTION AND WORK PERFORMANCE OF EMPLOYEES AS FACTORS IMPACTING WORK SAFETY (International Journal of Food and Nutritional Sciences, 2022)
Job satisfaction refers to an employee's overall happiness with their employment, which includes different characteristics such as the work environment, relationships with colleagues and supervisors, compensation, possibilities for growth, and the alignment of their abilities and interests with their tasks.Work performance refers to how well and quickly a person completes their job. It entails work quality, productivity, and the ability to meet deadlines and goals.